2010
DOI: 10.1002/ajmg.a.33587
|View full text |Cite
|
Sign up to set email alerts
|

Wiedemann–Steiner syndrome: Three further cases

Abstract: We describe three patients with a syndrome comprising arched, thick eyebrows, hypertelorism, narrow palpebral fissures, broad nasal bridge and tip, long philtrum, thin upper lip, stubby hands and feet, hirsutism, and severe psychomotor retardation. These patients expand the phenotype of the Wiedemann-Steiner syndrome and delineate it as an entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 8 publications
2
29
2
1
Order By: Relevance
“…S1 and Table S2). The same hand phenotype has been reported in one WSS patient although it is not known whether she has KMT2A abnormality. In addition, abnormal dermatoglyphics and prominent digit pads were frequently observed in our WSS patients but have not been previously reported.…”
Section: Resultssupporting
confidence: 70%
“…S1 and Table S2). The same hand phenotype has been reported in one WSS patient although it is not known whether she has KMT2A abnormality. In addition, abnormal dermatoglyphics and prominent digit pads were frequently observed in our WSS patients but have not been previously reported.…”
Section: Resultssupporting
confidence: 70%
“…Our patients shares several of the features of KMT2A -associated WSS, including postnatal growth retardation, developmental delay, wide nasal bridge, broad/bulbous nasal tip, and downslanted palpebral fissures [9,30]. They do not however have clear hypertrichosis cubiti, the clinical feature most readily associated - but not pathognomonic - with WSS.…”
Section: Discussionmentioning
confidence: 82%
“…Discussion WSS was first described in 1989 by Wiedemann et al (1989) with the case of a child with short stature, hypertelorism and other dysmorphic features and moderate developmental delay. A second case was identified by Steiner and Marques (2000), and several other cases of WSS have since been reported (Visser et al 2002;Koç et al 2007;Koenig et al 2010;Mendelsohn et al 2014). Jones et al (2012) identified heterozygous mutations of the MLL gene in five out of six children with clinical features of WSS.…”
Section: Resultsmentioning
confidence: 95%
“…Notably, also intragenic deletion and missense variations of the MLL gene have been recently reported as the molecular cause of phenotypes within the WSS-related clinical spectrum (Mendelsohn et al 2014;Strom et al 2014). Although Wiedemann's original description did not include hypertrichosis cubiti, this has been a consistent feature in most of the cases subsequently reported, including all the three discussed by Koenig et al (2010), and all five of those found to have mutations affecting MLL in Jones et al (2012). Notably, the sixth case of the study by Jones et al (2012) who had no MLL mutation was also the only one who did not display hairy elbows.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation